Pengembangan Bahan Ajar Pendidikan Jasmani Adaptif (Penjas Adaptif ) Bagi Anak Tunagrahita Ringan Di SLB Negeri Somba Opu Kabupaten Gowa - Meidina, Tatiana (PEMBELAJAR: Jurnal Ilmu Pendidikan, Keguruan, dan Pembelajaran, 2017)
This study aims to: (1) identification of the material characteristics of teaching physical education adaptive for mild mettally retarted children base class SLB Somba Opu district  Gowa  (2) completion of teaching materials physical education adaptive for mild mettally retarted children base class IV in SLB Somba Opu district  Gowa. The method used in research and development. Some stages will be done in research and development are: (1) Conduct preliminary research, (2) to collect data as a follow-up of preliminary research. (3) Develop an adaptive physical education teaching materials for mild mettally retarted children base class SLB Somba Opu district  Gowa, (4) Validation of products, (5) product revision post-validation, and (6) Conduct final testing of teaching materials. Product validation is done by subject matter experts and experts retarded. The instrument used in this study include: assessment sheet material experts and experts retarded and field notes. Based on the research and development needs to be concluded that the development of adaptive physical education teaching materials for mild mettally retarted children base class SLB Somba Opu district  Gowa  because it is not available at school from teachers and from the department of education. The results of the experimental study were developed with the characteristics of: (1) according to the scope of adaptive panning material (2) contextual, (3) using simple language, (4) concept visualization. This adaptive learning resource is developed by design: title page, introduction, table of contents, material, notes. Based on the experiment result of adaptive harvesting material obtained by result of improvement of capability of throwing and catching ball which means the instructional material developed is effective to improve the capability of children for light tunagrahita grade IV in SLB Somba Opu Gowa Regency.